RETRACTION: Factors Influencing the Severity of Diabetic Foot Ulcer in The Hospital: A Scoping Review - Editorial Board Indonesian Journal of Nursing & Health Care (Ammar Dharma Foundation, 2025)
This Retraction Notice concerns the article “Factors Influencing the Severity of Diabetic Foot Ulcer in The Hospital: A Scoping Review,” originally published in Indonesian Journal of Nursing & Health Care, Vol. 2(1), 2025, pp. 32–36. The article has been retracted following a formal complaint that identified substantial unattributed content taken from a private academic document shared for educational purposes only. An editorial investigation confirmed a breach of authorship ethics. In line with COPE guidelines, the Editorial Board has decided to retract the article to maintain scholarly integrity.